Organizational Communication Dynamics: A Literature Review on Enhancing Millennial Motivation in the Workplace - Elmanisar, Velnika; Utami, Batina Yulia; Syahril, Syahril; Kadri, Hanif Al (International Journal of Educational Dynamics, 2024)
The study aims to analyze how effective communication strategies can address generational challenges and align organizational goals with millennial aspirations. A library study method was employed, focusing on reviewing and synthesizing relevant literature to establish a comprehensive conceptual framework. The findings highlight several critical factors influencing millennial motivation, including dynamic message delivery, recognition of contributions through fair compensation, and the creation of a safe, supportive work environment. Additionally, applying human relations principles and fostering open communication between leadership and millennials were identified as key strategies for improving engagement and productivity. The study concludes that adaptive and innovative organizational communication approaches are essential for addressing the diverse needs of millennials, ensuring their active participation, and driving organizational success. By investing in effective communication, organizations can foster a harmonious and productive work environment that motivates millennials to contribute positively. These findings provide valuable insights for leaders and managers seeking to enhance workplace dynamics and support the professional growth of the millennial workforce.